Texts and Practices / Readings in Critical Discourse Analysis - Caldas-Coulthard Carmen Rosa; Coulthard Malcolm (Rouledge, 2003)
Preface, Critical Discourse Theory, On Critical Linguistics, The Representation of Social Actors, Technologisation of Discourse, Discourse and Power and Access, Texts and Practices: Critical Approaches, The Genesis of Racist Discourse in Austria Since 1989, Ethic and Racial and Tribal: The Language of Racism?, The Official Version: Audience Manipulation in Police Records of Interviews with Suspects, Conflict Talk in a Psychiatric Discharge Interview: Struggling Between Personal and Official Footings, Problems with the Representation of Face and its manifistetions in the discourse of the ''old-old'', Banking up the Wrong Tree? Male Hegemony and Discrimination Against Women and the reporting of Bestiality in the Zimbabwean Press, ''Women who Pay fo Sex and Enjoy It'': Transgression Versus Morality in Wmen's Magazines, Bibliography, Index.